Contribuição do modelo teórico-metodológico para a descrição semântico-argumentativa do discurso para a elaboração de instrumentos de avaliação da compreensão leitora em língua estrangeira - Schulz, Lisiane Ott (My University, 2018)
The goal of this study is to propose the didactic transformation of the Theoretical Methodological Model for the Semantic-Argumentative Description of the Discourse, by Tânia Maris de Azevedo, aiming at subsidizing the elaboration of an instrument devised to verify students’ reading comprehension proficiency in a foreign language. To achieve this goal, Saussure’s theoretical presuppositions are brought into discussion as well as the studies of Argumentative Semantics, especially Jean-Claude Anscombre and Oswald Ducrot's Theory of Polyphony, and Oswald Ducrot and Marion Carel's Theory of the Semantic Blocks, which serve as the basis for the Model. Furthermore, the concepts of reading and reading comprehension that support this research as well as the view on how to teach and evaluate this ability are also brought into consideration. In order to present the proposal, I introduce the studies on didactic transposition, by Yves Chevallard and Teodoro Álvarez, and the concept of didactic transformation, suggested by Azevedo. Finally, I make use of the formal mechanisms suggested by the Model to conduct the analysis and the semantic description of a discourse and make use of this description as a support for the planning and development of an instrument aimed at evaluating the reading comprehension ability. I believe that this transformation may show a possibility for teachers to qualify not only their own ability to reconstitute the meaning of a written discourse during the reading process but also their pedagogical practice related to teaching and assessing the development of that ability.
O objetivo deste estudo é propor a transformação didática do Modelo-Teórico Metodológico para a Descrição Semântico-Argumentativa do Discurso, de Tânia Maris de Azevedo, com vistas a subsidiar a elaboração de um instrumento de verificação da proficiência em compreensão leitora em língua estrangeira. Para alcançar esse objetivo, trago à discussão os pressupostos teóricos saussurianos, os estudos da Semântica Argumentativa, em especial a Teoria da Polifonia, de Jean-Claude Anscombre e Oswald Ducrot, e a Teoria dos Blocos Semânticos, de Oswald Ducrot e Marion Carel, que servem de fundamento para o referido Modelo e o apresento. Na sequência, discuto as concepções de leitura, de compreensão leitora, de ensino e de avaliação de tal habilidade que sustentam esta pesquisa. A fim de viabilizar a proposta, abordo os estudos sobre transposição didática, de Yves Chevallard e Teodoro Álvarez, e o conceito de transformação didática, sugerido por Azevedo. Realizo, enfim, com os mecanismos formais sugeridos pelo Modelo, a análise e a descrição semântica de um discurso e utilizo essa descrição como apoio para o planejamento e desenvolvimento de um instrumento de avaliação da compreensão leitora. Acredito que essa transformação possa mostrar uma possibilidade de o docente qualificar não apenas sua própria habilidade de reconstituir o sentido de um discurso escrito durante o processo de leitura como também o seu fazer pedagógico relacionado ao ensino e à avaliação do desenvolvimento dessa habilidade.
Keywords: Línguas modernas; Linguagem e línguas - Estudo e ensino; Compreensão na leitura; Semântica; Languages, Modern; Language and languages - Study and teaching; Reading comprehension; Semantics